Defining the attributes for specific playing positions in football match-play: A complex systems approach - Berber, E.; McLean, S.; Beanland, V.; Read, G. J. M.; Salmon, P. M. (Journal of Sports Sciences, 2020)
Talent identification and development programmes that retain and develop athletes are integral to the sporting success of National Governing Bodies in football. Currently, player attributes are studied in isolation without considering the complexity of interacting components of football performance. The current study applied a systems analysis framework to describe, in a structured and systematic way, the attributes for specific playing positions in football match-play. Methods: Eight high-level football coaches were interviewed. Models of the interacting attributes were developed for each position using Work Domain Analysis (WDA). Results: Six WDA models detail the attributes associated with each playing position. The models identified purposes of playing positions (restrict opposition actions, organise and coordinate, building up of offence, goal scoring and stretch opposition), performance-related measures and the functions required to achieve the playing position purposes (game play, psychological functions, time and space and player actions). Critically, the relationships between the purposes, measures, functions, processes, and objects are described in the models.